Critical review of condensable particulate matter - Feng, Yupeng; Li, Yuzhong; Cui, Lin (Fuel (Guildford), 2018)
•A diagram of the formation of condensable particulate matter (CPM) is created.•Method for measuring CPM and its improvements are systematically introduced.•Three factors that cause inaccuracies of CPM measurement are summarized.•Characteristics of condensable particulate matter are analyzed comprehensively.•This study proposes two recommended measures to control the emission of CPM. Particulate matter emitted by fuel combustion has become a major air pollutant. It comes in the form of filterable particulate matter (FPM) and condensable particulate matter (CPM). In the past, people focused on FPM due to its large emission amount. Such active research prompted the rapid development of FPM control technology. At present, FPM is effectively controlled, and its emission concentration is extremely low. By contrast, the emission concentration of CPM is higher than that of FPM and requires immediate attention. Therefore, people are paying close attention to CPM. Nevertheless, CPM is still poorly understood. On the basis of existing research, this study reviews CPM, including its concept, formation mechanism, and hazards. CPM test methods and the factors that affect the accuracy of CPM measurement are also discussed. Improvement methods focusing on CPM measurement are introduced. The results of previous research on CPM characteristics are summarized. Finally, possible CPM control techniques are discussed.